PERUBAHAN GAYA BERBUSANA ADAT KE PURA BAGI REMAJA HINDU BALI DI SMA NEGERI 5 DENPASAR - Kusuma Putra, Dewa Ngurah Tresna; Zuryani, Nazrina; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT The Changes of style in traditional dress to the Temple in SMA Negeri 5 Denpasar can be analyzed through sociology studies. This research seeks to discuss and explain about the causes of traditional dress style changes to Temple among Balinese Hindu adolescents today primarily students either boys and girls in SMA Negeri 5 Denpasar. This research uses explanative qualitative research method with analysis of consumption society theory of Jean P Baudrillard that is mark value and symbol value. Based on the results of this study it is known that the cause of the style changes in traditional dress to the Temple is influenced by several factors such as environmental influences, the influence of trend and fashion developments, the influence of economic conditions, the influence of public figures that exist in the community which resulted in a change of the values orientation ??in the use of customary dress to the temple which originally attach importance to the meaning value and philosophical values ?existing in customary dress to the temple which is now turned just into value of sign and value of symbol in order to get recognition, honor, social status, and the will to show identity, economic status, luxury when using traditional dress to the temple. Key Words: Change, Balinese Traditional Dress, Balinese Hindu Adolescent